Large‐Scale Climate Patterns Modulate Intraseasonal Mesoscale Activities in the Bay of Bengal - Zheen Zhang; Xueen Chen; Lequan Chi; Chunxin Yuan; Jie Zhang; Shuyan Zhang (Geophysical Research Letters)
Abstract By focusing on the intraseasonal mesoscale eddy kinetic energy, this study comprehensively distinguishes the influences of El Niño‐Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) on eddy activities in the Bay of Bengal. Altimetry records since 1993 show that intraseasonal mesoscale activities are enhanced in the middle (∼15°N) and southern bay approximately 6 months and 8 months after El Niño peaks, respectively, through the wave‐dominated approach. Meanwhile, influences from IOD manifest more rapidly and concentrate in the western bay, suggesting distinct mechanisms compared to those associated with ENSO. Further investigations reveal asymmetric effects linked to the phase of ENSO and IOD: positive ENSO events (El Niño) and negative IOD events are followed by enhanced intraseasonal mesoscale activities in the BoB, potentially triggered by the warmer background in the tropical Indian Ocean and the bay during these events, respectively. However, influences from the opposite phases are neglectable.